Análise da manutenção do torque e resistência à fratura após fadiga em parafusos de retenção confeccionados com diferentes metais para junções parafusadas de prótese sobre implante - Taborda, Maria Beatriz Bello [UNESP] (2018)
The objective of this study was to evaluate the effect of different metal alloys (Ti grade 2, Ti grade 4 and Ti grade 4 hard, Ti grade 5 - Ti6Al4V and surgical steel) used in the manufacture of retaining screws for UCLA abutments of hexagonal connection implants (HE) and Morse taper (CM), as well as mechanical cycling loading in the maintenance of torque and fracture resistance by electromechanical fatigue test by chewing followed by compression test. A total of 60 implants were used, 30 of CM connections and 4.0mm platform, and 30 of HE and 4.1mm platform, with their respective UCLA titanium abutments and retaining screws made of 5 different materials (n = 6): Ti grade 2, Ti grade 4 and Ti grade 4 hard, Ti grade 5 - Ti6Al4V and surgical steel (DSP® Biomedical). The implants were embedded in polyurethane with an inclination of 30 ° from a split matrix. Once embedded, they received the UCLA prosthetic metal abutments and retaining screws for each group and on them a metal cap fitted to the abutment, ensuring the application of the load on the longitudinal axis, in accordance with the ISO 14801 Technical Standard. Application of the torque recommended by the manufacturer, 20N for CM and 30N for HE, and the evaluation of the torque was used a digital torque meter. After an interval of three minutes of application of the initial torque, the initial torque (pre cycling) was measured. Then, the screws received a confirmation torque to be submitted to the electromechanical fatigue test by chewing in the mechanical cycling machine, and after that, the measurements of the final torque (post-cycling) were performed. The assemblies (implant / UCLA abutment / retaining screw / hemispherical loading device) were positioned on the mechanical cycling machine, set to operate in a total of 1x106 cycles, at the frequency of 2Hz, printing a dynamic...